90Y/177Lu-DOTATOC: From Preclinical Studies to Application in Humans - Licia Uccelli; Alessandra Boschi; Corrado Cittanti; Petra Martini; Stefano Panareo; Eugenia Tonini; Alberto Nieri; Luca Urso; Matteo Caracciolo; Luca Lodi; Aldo Carnevale; Melchiore Giganti; et al. (MDPI AG, 2021)
The PRRT (Peptide Receptor Radionuclide Therapy) is a promising modality treatment for patients with inoperable or metastatic neuroendocrine tumors (NETs). Progression-free survival (PFS) and overall survival (OS) of these patients are favorably comparable with standard therapies. The protagonist in this type of therapy is a somatostatin-modified peptide fragment ([Tyr3] octreotide), equipped with a specific chelating system (DOTA) capable of creating a stable bond with β-emitting radionuclides, such as yttrium-90 and lutetium-177. In this review, covering twenty five years of literature, we describe the characteristics and performances of the two most used therapeutic radiopharmaceuticals for the NETs radio-treatment: [90Y]Y-DOTATOC and [177Lu]Lu-DOTATOC taking this opportunity to retrace the most significant results that have determined their success, promoting them from preclinical studies to application in humans.